A new model for non-typeable Haemophilus influenzae middle ear infection in the Junbo mutant mouse - Derek Hood; Richard Moxon; Tom Purnell; Caroline Richter; Debbie Williams; Ali Azar; Michael Crompton; Sara Wells; Martin Fray; Steve D. M. Brown; Michael T. Cheeseman (The Company of Biologists, 2016)
Acute otitis media, inflammation of the middle ear, is the most common bacterial infection in children and, as a consequence, is the most common reason for antimicrobial prescription to this age group. There is currently no effective vaccine for the principal pathogen involved, non-typeable Haemophilus influenzae (NTHi). The most frequently used and widely accepted experimental animal model of middle ear infection is in chinchillas, but mice and gerbils have also been used. We have established a robust model of middle ear infection by NTHi in the Junbo mouse, a mutant mouse line that spontaneously develops chronic middle ear inflammation in specific pathogen-free conditions. The heterozygote Junbo mouse (Jbo/+) bears a mutation in a gene (Evi1, also known as Mecom) that plays a role in host innate immune regulation; pre-existing middle ear inflammation promotes NTHi middle ear infection. A single intranasal inoculation with NTHi produces high rates (up to 90%) of middle ear infection and bacterial titres (104-105 colony-forming units/µl) in bulla fluids. Bacteria are cleared from the majority of middle ears between day 21 and 35 post-inoculation but remain in approximately 20% of middle ears at least up to day 56 post-infection. The expression of Toll-like receptor-dependent response cytokine genes is elevated in the middle ear of the Jbo/+ mouse following NTHi infection. The translational potential of the Junbo model for studying antimicrobial intervention regimens was shown using a 3 day course of azithromycin to clear NTHi infection, and its potential use in vaccine development studies was shown by demonstrating protection in mice immunized with killed homologous, but not heterologous, NTHi bacteria.